2022
DOI: 10.3390/molecules27113630
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Dihydroisocoumarin Isolated from Wadi Lajab Sediment-Derived Fungus Penicillium chrysogenum: In Vitro and In Silico Study

Raha Orfali,
Shagufta Perveen,
Mohamed Fahad AlAjmI
et al.

Abstract: Antibiotic resistance is considered a major health concern globally. It is a fact that the clinical need for new antibiotics was not achieved until now. One of the most commonly prescribed classes of antibiotics is β-Lactam antibiotics. However, most bacteria have developed resistance against β-Lactams by producing enzymes β-Lactamase or penicillinase. The discovery of new β-Lactamase inhibitors as new antibiotics or antibiotic adjuvants is essential to avoid future catastrophic pandemics. In this study, five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…It is known that various polyketides, including antibiotics (penicillins), extrolites and penicillic acids, are produced by halophilic strains of Penicillium [ 52 ] and that, antimicrobial compounds such as β-lactam antibiotics from P . chrysogenum and other Penicillium species inhibit most Gram-positive bacteria [ 53 ]. In the light of this existing knowledge, the further characterization and purification of the active metabolites produced by the above six strains of P .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that various polyketides, including antibiotics (penicillins), extrolites and penicillic acids, are produced by halophilic strains of Penicillium [ 52 ] and that, antimicrobial compounds such as β-lactam antibiotics from P . chrysogenum and other Penicillium species inhibit most Gram-positive bacteria [ 53 ]. In the light of this existing knowledge, the further characterization and purification of the active metabolites produced by the above six strains of P .…”
Section: Discussionmentioning
confidence: 99%
“…The isolates P. citrinum NM-3 and A. subalbidus NM-18, NM-19, NM-20, NM-23 and NM-24) proved to be active against the Gram-positive bacteria E. faecalis, M. luteus, S. aureus, S. epidermidis and MRSA, the Gram-negative bacteria E. coli and S. Typhi, the yeast C. albicans and also the human pathogenic fungus A. fumigatus. It is known that various polyketides, including antibiotics (penicillins), extrolites and penicillic acids, are produced by halophilic strains of Penicillium [52] and that, antimicrobial compounds such as β-lactam antibiotics from P. chrysogenum and other Penicillium species inhibit most Gram-positive bacteria [53]. In the light of this existing knowledge, the further characterization and purification of the active metabolites produced by the above six strains of P. citrinum and A. subalbidus are being investigated.…”
Section: Plos Onementioning
confidence: 99%
“…The endophytes P. canescens and P. commune showed antimicrobial activities against to the human pathogens ( Gao et al, 2011 ; Malhadas et al, 2017 ) and the phytopathogenic fungi ( Bertinetti et al, 2009 ). Other species, such as P. cinnamopurpureum ( Dinesh et al, 2022 ), P. chrysogenum ( Orfali et al, 2022 ), and P. citrinum ( Kumari et al, 2021 ), had also been reported as being prolific producers of antimicrobial compounds. However, no studies have reported the antibacterial activity of P. macrosclerotiorum , which was identified as a new species of the genus Penicillium in 2017 ( Wang et al, 2007 ; Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Orfali et al ( 2022 ) investigated compounds (177–181) obtained from Wadi Lajab sediment-derived fungus P. chrysogenum for their antimicrobial activity with comparison with five types of pathogenic bacteria Staphylococcus aureus, Bacillus licheniformis, Escherichia fergusonii, Enterobacter xiangfangensis, and Ps. aeruginosa .…”
Section: Introductionmentioning
confidence: 99%